Propuesta de implementación del departamento de compras internacionales en la empresa BALDOCER LTDA (2022)
Baldocer Ltda. is a Colombian company with more than 10 years in the market dedicated to the commercialization and distribution of residential and institutional construction, remodeling and finishing materials, with a satisfactory reception in the market for offering innovative products of excellent quality, building customer loyalty. and exceeding the expectations of its customers. During the last five years, the company Baldocer Ltda has presented a growth of 40% in its profits, which is why the company has decided to explore the feasibility of importing its products directly from manufacturers to save costs and optimize resources without having to resort to distributors in the country. From this perspective, with this work it is intended to present to the company Baldocer Ltda a proposal for the implementation of the international purchasing department in the company located in the city of Bogotá D.C that allows it to carry out the process of importing merchandise directly from suppliers in the outside. For this, in the first place, a diagnosis was made on the current state of the company Baldocer Ltda in terms of commercialized references of international origin. Next, the technical and legal criteria necessary for the implementation of an international purchasing department in the company were described, and finally the organizational structure of the international purchasing department for the company Baldocer Ltda was defined, including the international purchasing procedure and profile of charges required for this department.